Perilaku Cyberloafing: Perspektif Faktor Individual dan Organisasi di Dinas Pendidikan dan Kebudayaan Kota Malang - Sunaryati Hardiani; Guanting Guanting; Chodidjah Chodidjah; Abdul Malik Kumar (University of Merdeka Malang, 2022)
The purpose of this study was to analyze the influence of individual factors and organizational factors on the cyberloafing behavior of employees at the Malang City Education and Culture Office. Data was collected by census through questionnaires distributed online via google form. Multiple linear regression analysis, proves that individual factors from work stress and organizational factors from the work environment have a positive and significant effect on cyberloafing behavior. For this reason, in order to reduce the cyberloafing behavior of its employees, the Malang City Education and Culture Office must have a written rule that prohibits its employees from carrying out cyberloafing activities during working hours, because this is very important so that employees do not arbitrarily carry out cyberloafing activities. it needs to be accompanied by sanctions.